Dynamic conformal arc cranial stereotactic radiosurgery: implications of multileaf collimator margin on dose–volume metrics - Tanyi, J A (The British Institute of Radiology., 2012)
OBJECTIVE: The effect of multileaf collimator (MLC) margin on target and normal tissue dose–volume metrics for intracranial stereotactic radiosurgery (SRS) was assessed. METHODS: 118 intracranial lesions of 83 SRS patients formed the basis of this study. For each planning target volume (PTV), five separate treatment plans were generated with MLC margins of −1, 0, 1, 2 and 3 mm, respectively. Identical treatment planning parameters were employed with a median of five dynamic conformal arcs using the Varian/BrainLab high-definition MLC for beam shaping. Prescription dose (PD) was such that 22 Gy covered at least 95% of the PTV. Dose–volume and dose–response comparative metrics included conformity index, heterogeneity index, dose gradient, tumour control probability (TCP) and normal tissue complication probability (NTCP). RESULTS: Target dose heterogeneity decreased with increasing MLC margin (p<0.001); mean heterogeneity index decreased from 70.4±12.7 to 10.4±2.2%. TCP decreased with increasing MLC margin (p<0.001); mean TCP decreased from 81.0±2.3 to 62.2±1.8%. Normal tissue dose fall-off increased with MLC margin (p<0.001); mean gradient increased from 3.1±0.9 mm to 5.3±0.7 mm. NTCP was optimal at 1 mm MLC margin. No unambiguous correlation was observed between NTCP and PTV volume. Plan delivery efficiency generally improved with larger margins (p<0.001); mean monitor unit per centigray of the PD decreased from 3.60±1.30 to 1.56±0.13. CONCLUSION: Use of 1 mm MLC margins for dynamic conformal arc-based cranial radiosurgery resulted in optimal tumour control and normal tissue sparing. Clinical significance of these comparative findings warrants further investigation.